Governing the invisible commons: Ozone regulation and the Montreal Protocol. Issue 2 (August 2014) - Epstein, Graham; Pérez, Irene; Schoon, Michael; Meek, Chanda L.
The Montreal Protocol is generally credited as a successful example of international cooperation in response to a global environmental problem. As a result, the production and consumption of ozone-depleting substances has declined rapidly, and it is expected that atmospheric ozone concentrations will return to their normal ranges toward the end of this century. This paper applies the social-ecological system framework and common-pool resource theory to explore the congruence between successful resolution of small-scale appropriation problems and ozone regulation, a large-scale pollution problem. The results of our analysis correspond closely to past studies of the Protocol that highlight the importance of attributes such as a limited number of major industrial producers, advances in scientific knowledge, and the availability of technological substitutes. However, in contrast to previous theoretical accounts that focus on one or a few variables, our analysis suggests that its success may have been the result of interactions between a wider range of SES attributes, many of which are associated with successful small-scale environmental governance. Although carefully noting the limitations of drawing conclusions from the analysis of a single case, our analysis reveals the potential for fruitful interplay between common-pool resource theory and large-scale pollution problems.